1997
DOI: 10.3354/meps159209
|View full text |Cite
|
Sign up to set email alerts
|

Physiological versus viscosity-induced effects of water temperature on the swimming and sinking velocity of larvae of the serpulid polychaete Galeolaria caespitosa

Abstract: Water viscosity is inversely related to water temperature. Because marine invertebrate larvae generally operate in a hydrodynamic environment dominated by viscous forces (i.e. Reynolds numbers < l ) , temperature-induced changes in water viscosity may exert profound influence on the swimming and sinking velocity of larvae. Wh~lst the physiological effects of water temperature on larval locomotion have received considerable experimental investigation, the influence of temperatureinduced changes in water viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 10 publications
5
16
0
Order By: Relevance
“…This statement is in agreement with Podolsky & Emlet (1993) who found that the swimming velocity of larvae of the sand dollar Dendraster excentricus was reduced by about 40% when the temperature was reduced from 22 to 12°C, and about 40% of this decrease could be ascribed to the increase in viscosity. Similar results were obtained by Bolton & Havenhand (1997) who studied the viscosity-induced effects of water temperature on the swimming velocity of larvae of the polychaete Galeolaria caespitosa. On average, about half the decline in swimming velocity was found to be caused by mechanical effects of increased viscosity while the remainder was presumed to be due to physiological effects.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…This statement is in agreement with Podolsky & Emlet (1993) who found that the swimming velocity of larvae of the sand dollar Dendraster excentricus was reduced by about 40% when the temperature was reduced from 22 to 12°C, and about 40% of this decrease could be ascribed to the increase in viscosity. Similar results were obtained by Bolton & Havenhand (1997) who studied the viscosity-induced effects of water temperature on the swimming velocity of larvae of the polychaete Galeolaria caespitosa. On average, about half the decline in swimming velocity was found to be caused by mechanical effects of increased viscosity while the remainder was presumed to be due to physiological effects.…”
Section: Introductionsupporting
confidence: 85%
“…Bolton & Havenhand (1997, their Table 2), for example, found a 31% reduction in swimming velocity of small (posthatched) larvae of the serpulid polychaete Galeolaria caespitosa in response to a 20.6% increase in viscosity by inert polymer (Ficoll) addition at 25°C. However, the decrease in swimming velocity was 60.4% in response to a lowering of the temperature of seawater from 25 to 15°C, which gave the same 20.6% increase in viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…Polychaete larvae are less likely to be disrupted because of their faster swimming speeds, e.g. 4 mm s −1 in metatrochophores of G. caespitosa (Bolton & Havenhand 1997). Once larvae are crawling on the substratum, they could be more easily affected by ciliate movements and currents.…”
Section: Effects Of Ciliates On Larval Settlementmentioning
confidence: 99%
“…It is therefore difficult to differentiate between the direct effect of temperature and the indirect effect of viscosity on the swimming activity of Temora longicornis. However, previous results have indicated environmental changes in viscosity associated with temperature can influence the small-scale processes of marine zooplanktonic organisms (Po dolsky & Emlet 1993, Bolton & Havenhand 1997, even in free-swimming copepods (Larsen et al 2008). Thus, the observed de crease in swimming velocity could have been the result of an adaptation to increased viscosity, which would have involved an increase in the energy required to move the swimming appendages or a mechanical hindrance of the appendages.…”
Section: Mechanical Constraintsmentioning
confidence: 75%